Nuclear Security Culture and BATAN’s Assessment: BATAN’s Experience - Anhar R. Antariksawan (International Journal of Nuclear Security, 2016)
Organizations should increase safety to minimize the harmful effects of nuclear materials. Additionally, organizations should take measures to protect security culture within the organization itself. This paper covers the National Nuclear Energy Agency of Indonesia’s (BATAN’s) promotion of nuclear security culture and self- assessment projects, which is based on the International Atomic Energy Agency’s (IAEA) methodology.
Keywords: security; security culture; self-assessment